Neurological aspects at children with a perinatal HIV-infection - M. Yu. Fomina; E. E. Voronin (Журнал инфектологии)
In the given research results of inspection of children with a HIV-infection are analyzed at perinatal ways. 550 children from a birth till 10 years are surveyed. The neurological status of patients, the data immunological and virologic inspection of plasma and cerebrospinal fluid is studied. It is spent neuroimaging and psychometric testing. It is shown that defeat of nervous system is HIV-infection display at children’s age. A HIV-induced defeat of the central and peripheral nervous system is presented, first of all, to specific HIV-encephalitis with sharp and sub acute a current. Are revealed clinical and immunological correlations at various stages of infectious process, influence antiretroviral therapies on dynamics of neurological infringements is analyzed.